The Influence of Gadget Use on the Social and Emotional Behavior of Elementary School Students - Suci Purwatiningsih; Tubagus Pamungkas; Zulkifli Zulkifli (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze the influence of gadget use on the social and emotional behavior of students at SD Negeri 019 Sagulung Batam. The study employed a mixed methods approach with a sequential explanatory design, in which quantitative data collection was followed by qualitative data collection. Quantitative data were obtained through questionnaires distributed to students, while qualitative data were collected through interviews, observations, and documentation to strengthen the research findings. Data analysis was conducted using a significance test with a significance level of α = 5%. The results showed that gadget use did not have a significant influence on students’ emotions, with a significance value of 0.431. However, gadget use had a significant influence on students’ attitudes, with a significance value of 0.009. The findings indicate that gadget use has both positive and negative impacts on students’ social and emotional behavior, particularly in the learning process and social interaction. Based on the findings, educational policies are needed to support the wise use of gadgets through character education strengthening and collaboration between schools and parents in supervising students’ gadget use.